The Impact of Clinical Practice Stress on Nursing Professional Competence among Undergraduate Nursing Students: A Cross-Sectional Study - Pei-Ling Wu (AVES, 2024)
Aim: This study aims to explore the impact of undergraduate nursing students' clinical practice stress on nursing professional competence. Methods: The research was performed as a cross-sectional study. From January 2023 to February 2023, a total of 114 nursing students in their first clinical practice at a university in Taiwan were included in the survey. Data collection was conducted using the Clinical Practice Stress Scale and the Nurse Professional Competence Scale. Pearson's correlation analysis was used to analyze the relationship between clinical practice stress and nursing professional competence, and multiple regression analysis was used to explore predictors of nursing professional competence. Results: The clinical practice stress of nursing students was at a medium level (37.75 ± 12.24), and the nurse professional competence was at a high level (79.34 ± 10.12). Clinical practice stress was negatively correlated with nurse professional competence (r=−.311, p=.001). Clinical practice stress could predict nursing professional competence (F=3.041, p=.013), which explained 12.3% of the total variance (adjusted R2 = .083, p < .001), among which the stress of taking care of patients in clinical practice had the highest β value (β=−.336, p=< .001). Conclusion: Clinical practice stress can predict nursing professional competence. The stress of taking care of patients in clinical practice is a major predictor of nursing professional competence. Nursing students who experience the stress of clinical practice tend to develop lower nursing professional competence, highlighting the need for effective coping strategies and supportive learning environments for nursing students.